2009
DOI: 10.3174/ajnr.a1727
|View full text |Cite
|
Sign up to set email alerts
|

Brain Structural Variability due to Aging and Gender in Cognitively Healthy Elders: Results from the São Paulo Ageing and Health Study

Abstract: BACKGROUND AND PURPOSE:Several morphometric MR imaging studies have investigated age-and sex-related cerebral volume changes in healthy human brains, most often by using samples spanning several decades of life and linear correlation methods. This study aimed to map the normal pattern of regional age-related volumetric reductions specifically in the elderly population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 31 publications
6
42
0
1
Order By: Relevance
“…The location of these foci of inverse correlation is highly consistent with our current VBM findings and with data obtained in an expanded sample of subjects recruited from the same pool of elderly individuals investigated in the present PET study. 43 When we applied PVE correction to our PET data, none of the abovementioned significant correlations between FDG uptake and aging remained significant. Taken together, our findings of brain metabolic reductions due to aging are largely secondary to GM atrophy and that despite the volume loss that characterizes the aging process, the remaining cerebral tissue is shown to have a normal glucose consumption rate in cognitively healthy elders.…”
Section: Discussionmentioning
confidence: 99%
“…The location of these foci of inverse correlation is highly consistent with our current VBM findings and with data obtained in an expanded sample of subjects recruited from the same pool of elderly individuals investigated in the present PET study. 43 When we applied PVE correction to our PET data, none of the abovementioned significant correlations between FDG uptake and aging remained significant. Taken together, our findings of brain metabolic reductions due to aging are largely secondary to GM atrophy and that despite the volume loss that characterizes the aging process, the remaining cerebral tissue is shown to have a normal glucose consumption rate in cognitively healthy elders.…”
Section: Discussionmentioning
confidence: 99%
“…The GM volume decrease observed in healthy subjects during aging that diffusely affects the cerebral cortex may preferentially involve the associative neocortex, particularly the prefrontal and temporal regions [25][26][27][28] and the medial frontal cortex. 28 Although the GM changes detected in subcortical and cortical areas may be secondary to our patients' involuntary neck movements, this possibility seems unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Neural deterioration is a plausible account for our results as well. Investigating neural structures is outside the scope of this study, but there is evidence of linear structural reductions in the volume of the amygdala throughout the adult life span (Curiati et al, 2009;Giorgio et al, 2010;Mu, Xie, Wen, Weng, & Shuyun, 1999;Peelle, Cusack, & Henson, 2012;Walhovd et al, 2005;Walhovd et al, 2011), and neuropsychological research using the same stimuli and task as the present study has shown that the integrity of this structure is critical for the perception of fear and sadness in music (Gosselin et al, 2005(Gosselin et al, , 2007. This would also be in agreement with the hypothesis put forward by Cacioppo et al (2011) that deterioration in the amygdala might be the origin of dampened responses to negative information at older ages (but for arguments claiming relatively preserved amygdala functioning, see Mather & Carstensen, 2005;Reed & Carstensen, 2012).…”
Section: Aging and Emotion Recognition In Musicmentioning
confidence: 99%